2016
DOI: 10.20849/abr.v1i2.78
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Effects of Foreign Ownership on Innovation

Abstract: In developing countries, government actively promotes foreign investment in order to adapt the new and latest technology. This leads to greater R&D activities, thus this creates knowledge and technology spillover. In this paper, we look at Korea where the R&D has been the main factor of rapid growth. We study the effects of foreign ownership on technological performance by looking at 756 R&D intensive Korean firms from 1999 to 2009. We look the number of applied and registered patents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…This result also informs the international business literature that reports mixed findings on the effects of foreign ownership on local innovation performance (Love, Ashcroft, & Dunlop, ; Lee & Yang, ). Lee and Yang (), for instance, found that foreign ownership structures had a significant effect on a local firm's ability to innovate, while other studies found otherwise (e.g., Knell & Srholec, ). It is quite possible that these mixed results could be due to the lack of detailed investigation on the type of R&D activity performed by the local firm.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result also informs the international business literature that reports mixed findings on the effects of foreign ownership on local innovation performance (Love, Ashcroft, & Dunlop, ; Lee & Yang, ). Lee and Yang (), for instance, found that foreign ownership structures had a significant effect on a local firm's ability to innovate, while other studies found otherwise (e.g., Knell & Srholec, ). It is quite possible that these mixed results could be due to the lack of detailed investigation on the type of R&D activity performed by the local firm.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, local firms may lose the opportunity to access the foreign technologies when the MNCs hesitate to share their knowledge. Instead, it is more likely for MNCs to transfer foreign knowledge to local businesses when they have equity investments through varying degrees of ownership stake in local firms (Djankov & Hoekman, ; Javorcik, ; Lee & Yang, ). By foreign knowledge, we refer to the product and process knowledge developed overseas accessible through FDIs from MNCs (Blomström & Sjöholm, ; Sasidharan & Kathuria, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ezt a különbséget Falk az új tagországok külföldi tulajdonú cégeinek alacsonyabb átlagéletkorával magyarázta. Lee-Yang [2016] a kilencvenes évek eleje és a kétezres évek eleje közötti időszakot felölelő dél-koreai minta alapján pozitív összefüggést talált a külföldi tulajdon és az innovációs teljesítmény között (amit a szabadalmak számával mért). Ezt a szerzőpáros azzal indokolta, hogy a fejlett országokból egyre több magasan kvalifikált befektető érkezett a kezdeti időszakban a még viszonylag fejletlenebbnek számító országba, és hozott fejlett technológiát, ami több K + F-tevékenységhez és a bejegyzett szabadalmak számának növekedéséhez vezetett.…”
Section: Szakirodalmi áTtekintés a Termelékenység Az Export éS Az Inn...unclassified